Scope of technology in health care, special focus on nursing - Adil Mudasir Malla; Ulfat Amin (Wolters Kluwer Medknow Publications, 2023)
Integrating artificial intelligence (AI) into health care reshapes nursing practices and education, enhancing patient care and clinical processes. This article discusses the transformative potential of AI in nursing, from streamlining documentation and diagnosis using AI applications to the evolution of nursing. The utilization of AI in primary care through automated communication strategies and the emergence of humanistic AI solutions are explored. As nurses adapt to AI-driven health-care technologies, balancing present needs with future demands becomes imperative. AI provides substantial advantages, but it's crucial to address challenges to ensure the successful integration of technology in healthcare and maintain the delivery of high-quality patient care in our tech-driven healthcare environment.